Growth dynamics of Geoffroea decorticans and Parkinsonia praecox and their response to climate in arid and semiarid environments in Argentina = Dinámica de crecimiento y relación con el clima de Geoffroea decorticans y Parkinsonia praecox en ambientes áridos y semiáridos de Argentina - Cendoya, María Alicia; Micca, Marcia; Bogino, Stella Marys (Facultad de Ciencias Forestales y Recursos Naturales, Universidad Austral de Chile, 2021)
Arid and semiarid environments dominate the Earth’s surface and are very vulnerable to global change. Chañar (Geoffroea decorticans) and brea (Parkinsonia praecox) are two ubiquitous woody species of these environments. They grow in degraded forests, strongly modified areas and as a main component of secondary forests. Despite the value of both species, little is known about their growth dynamics and their relationship with climate. The objective of this research was to determine their dendrochronological potential and the connection between growth and climate variables. Anatomical and standard dendrochronological methods were applied. First of all, we stated the anatomical characteristics that allowed us to detect tree-ring boundaries (terminal parenchyma and variation in the shape of vessels). Further, after dating and measurement of tree rings we determined significant correlation between series, which means a common growth signal among trees as a result of environmental variable effects. Trees were not older than 40 years. Mean annual radial growth was 3.37 mm (SD±0.71) and 2.16 mm (SD±0.61) for chañar and brea, respectively. Finally, chañar and brea had a negative growth-mean temperature association. Rainfall affected chañar and brea growth in summer previous to the growing season. Southern Oscillation Index (SOI) had an inverse association with growth of brea. This means, in the case of brea, a significant association with local (temperature and rainfall) and global (SOI) climate variables. These results evidenced the growth dynamics of both species and their value for dendroclimatological studies for the first time.